Pengaruh Citra Merk Ngubi terhadap Minat Beli Pelanggan: Studi pada Pelanggan Ngubi Kota Bandung - Aprilia Utami Herdi, Aprilia Utami Herdi; Widwi Handari Adji, Widwi Handari Adji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted on its own business, namely Ngubi Bandung city to test and analyze brand image of customer interest in the business Nubi Bandung city with a population of 300 and a sample of 75 respondents. The data obtained with the influence of brand image on consumer buying interest is consumer perception. Based on all the resulting data that has been obtained and processed, the researcher found that the brand image of Nubi has a very high/strong and positive influence so that it has a direct relationship with the value of Interest in Buying Ngubi Products. Where Brand Image is able to influence 86.5% of consumers' buying interest in Ngubi Products. This shows that competition in the f&b sector is quite tight and provides business opportunities. Not only the brand must be unique, the food must also be unique in order to get repeat purchases.